Social Inequalities Along the Childhood Cancer Continuum: An Overview of Evidence and a Conceptual Framework to Identify Underlying Mechanisms and Pathways - Erdmann, Friederike; Feychting, Maria; Mogensen, Hanna; Schmiegelow, Kjeld; Zeeb, Hajo (Frontiers in Public Health, 2019)
Inequalities in health according to social conditions are regarded as unnecessary and unjust. There is a large body of evidence on inequalities in adult cancer, observable throughout the societies on a national level as well as on a global scale. Socioeconomic influences on health matter at all ages including childhood, for which childhood cancer is the leading cause of disease related death in high-income countries (HICs). Substantial differences in the reported incidence of childhood cancers have been observed globally by socioeconomic development of a population. This is reflected in the higher incidence rates reported for HICs, particularly for acute lymphoblastic leukemia, and for cancer in infants (below 1 year), compared to low- and middle-income countries (LMICs). Considerable inequalities between populations and degree of socioeconomic development are also noted for survival from childhood cancer, with substantially lower survival rates seen in most LMICs compared to HICs. With respect to inequalities by socioeconomic position (SEP) within countries, findings of an association between SEP and childhood cancer risk are diverse and limited to studies from HICs. On the contrary, observations on social inequalities in survival within countries are accumulating and indicate that survival inequalities do not only concern resource-poor countries but also high-income populations including European countries. In turn, a childhood cancer diagnosis in itself may have implications on the parents' socioeconomic situation as well as on the later socioeconomic life after having survived the disease. The underlying mechanisms and causal pathways of these empirically demonstrated social inequalities are poorly understood, although it is of significant public health relevance for any actions or strategies to reduce childhood cancer-related inequity. We propose a conceptual framework on potential underlying mechanism and pathways specifically addressing social inequalities in childhood cancer and after childhood cancer to (i) illustrate potential pathways by which social determinants may create health inequities at different points of the childhood cancer continuum; (ii) illustrate potential pathways by which a childhood cancer diagnosis may impact the socioeconomic situation of the concerned family or the later life of a childhood survivor; and (iii) point out how major determinants may relate to each other.